Exploring Teacher’s Feedback on Students’ Writing Skill in Indonesian EFL Classroom - Syahrianti Syahrianti; Saiful Gaffar; Sahril Nur; Mayra C. Daniel (English Department FBS UNP, 2023)
This research was based on the phenomenon in school where many students find writing challenging. The students do not know if their writing is correct since they are too shy to ask the teacher when they have problems. In addition, students lack enthusiasm to learn writing because the class was unattractive. This research aimed to find out the teacher’s written feedback in students' written tasks and the factors of good teacher’s written feedback completed by teachers, teacher barriers, and students’ responses to written feedback in the second semester of tenth grade at SMA Islam Athirah 1 Makassar in 2021/2022. This was qualitative research. The data were evaluated utilizing data reduction, data display, and data conclusion. This investigation involved tenth graders at SMA Islam Athirah 1 Makassar. This research sampled 32 students from one class, X IPA 2. The researcher collected data via instruments, interviews, questionnaires, and document examination. From the data analysis, it was observed that the teacher rarely met all three aspects. Many challenges that teachers had in offering written feedback and students lacked reaction in the second semester of tenth grade at SMA Islam Athirah 1 Makassar.